Metformin attenuates vascular pathology by increasing expression of insulin-degrading enzyme in a mixed model of cerebral amyloid angiopathy and type 2 diabetes mellitus. (25th September 2021) - Inoue, Yasuteru; Masuda, Teruaki; Misumi, Yohei; Ando, Yukio; Ueda, Mitsuharu
Graphical abstract: Highlights: Metformin reduced cerebral Aβ in APP23- ob/ob mice and mixed model CAA-T2DM mice.. Metformin reduced hippocampal and cortical soluble and insoluble Aβ42 and Aβ40. Metformin increased levels of hippocampal IDE. Metformin attenuated CAA severity by enhancing Aβ-cleaving IDE expression. Metformin may be a new therapeutic strategy in CAA, especially for T2DM patients. Abstract: Sporadic cerebral amyloid angiopathy (CAA), which is characterized by cerebrovascular amyloid β (Aβ) deposits, causes cerebral hemorrhages and dementia in elderly people. Metformin has been used to treat patients with type 2 diabetes mellitus (T2DM), and animal and clinical studies have reported therapeutic effects of metformin in Alzheimer's disease (AD). However, the therapeutic effects of metformin in CAA are unclear. Here, we used a mixed mouse model of CAA and T2DM (APP23- ob/ob ) to investigate whether metformin has therapeutic effects on cerebrovascular Aβ deposits. We dissolved metformin hydrochloride in water and administered it orally at 350 mg/kg/day. Treatments started when mice were 6 weeks old and continued until they were 15 months old. After we treated APP23- ob/ob mice with metformin, we counted the numbers of vessels with Aβ and measured levels of Aβ40 and Aβ42 (soluble and insoluble), amyloid precursor protein (APP), APP-processing enzymes (α-, β-, and γ-secretases), and Aβ-degrading enzymes (insulin-degrading enzyme [IDE], neprilysin). Metformin significantly reduced cerebrovascular Aβ deposits in APP23- ob/ob mice ( p  < .05). Compared with controls, metformin-treated APP23- ob/ob mice had significantly reduced Aβ levels in the cerebral cortex ( p  < .05) and hippocampus ( p  < .05) and increased levels of IDE in the hippocampus ( p  < .01). Our results indicate that metformin attenuates the severity of CAA by enhancing Aβ-cleaving IDE expression. The clinical application of metformin may lead to a novel therapeutic strategy in CAA treatment, especially in patients with T2DM.